Revision of zigzag geckos (Diplodactylidae: Amalosia) in eastern Australia, with description of five new species - Hoskin, Conrad. J.; Couper, Patrick J. (Zootaxa, 2023)
Geckos of the genus Amalosia Wells & Wellington, 1984 occur across eastern and northern Australia. Only five species are described but additional diversity has been recognised for some time. Here we assess species diversity in eastern Australia, using morphological and genetic (ND4 mtDNA) data. We describe five new species, all morphologically distinct and highly genetically distinct (>25% divergence). Amalosia hinesi sp. nov. is found in woodlands on the western side of the Great Dividing Range in south-east Queensland and north-east New South Wales. Amalosia saxicola sp. nov. is a large species found on rocks in the Mackay–Townsville areas of mid-east Queensland, including on many offshore islands. Amalosia nebula sp. nov. is restricted to rocky areas in upland sclerophyll forest of the Wet Tropics region of north-east Queensland. Amalosia capensis sp. nov. is a small species found in the northern half of Cape York Peninsula. Amalosia queenslandia sp. nov. is a small species that is widespread through woodlands over much of eastern and central Queensland. These species are diagnosed from other Amalosia species in eastern Australia, including A. cf. rhombifer which occurs in north-western Queensland. Amalosia cf. rhombifer is part of the clades comprising the remainder of the ‘A. rhombifer’ complex across the Northern Territory and Western Australia, which will be dealt with separately. Herein, we also we also synonymise the monotypic genus Nebulifera with Amalosia. This revision brings the number of Amalosia species to ten.